LEGAL REASONING PEREMPUAN DALAM PERKARA GUGAT CERAI DI PENGADILAN AGAMA KUDUS TAHUN 2014 - Lina Kushidayati (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2015)
This article focuses on legal reasoning proposed by female litigants in divorce cases in Religious Court of Kudus (PA Kudus), Cetral Java during 2014. There are 12 (twelve) cases chosen randomly from institutional website www.badilag.net. Those cases were analyzed to understand the reasons behind the divorce cases. Hermeneutic is a usefull theory in this article.